2012
DOI: 10.5005/johcd-6-1-18
|View full text |Cite
|
Sign up to set email alerts
|

Barodontalgia: A Clinical Entity

Abstract: Barodontalgia is the oral pain caused by the changes in the pressure caused due to altitude changes either on deep sea diving or inflight conditions. Barodontalgia is one of the important clinical entities which present with such overlapping signs and symptoms, that in normal clinical setup the pain due to barodontalgia goes unnoticed. Also the literature available in textbooks is also less informative and revealing of the nature of pain caused due to barodontalgia. Hence this article focuses on those untouche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In addition, this better dental care might itself decrease the risk for barodontolagia [24][25][26] and decrease the incidence of chronic pulpitis, another known cause for barodontalgia among patients exposed to barometric changes. 27,28 F I G U R E 2 Percentage of retreated restorations-composite vs amalgam in the study and control groups 0.0% These findings indicate that further research should be conducted, adjusting the rate of dental follow-ups according to diving frequency and considering socioeconomic status. When dealing with military divers, dental examinations should be considered part of their medical competency before operations.…”
Section: Re Sultsmentioning
confidence: 84%
“…In addition, this better dental care might itself decrease the risk for barodontolagia [24][25][26] and decrease the incidence of chronic pulpitis, another known cause for barodontalgia among patients exposed to barometric changes. 27,28 F I G U R E 2 Percentage of retreated restorations-composite vs amalgam in the study and control groups 0.0% These findings indicate that further research should be conducted, adjusting the rate of dental follow-ups according to diving frequency and considering socioeconomic status. When dealing with military divers, dental examinations should be considered part of their medical competency before operations.…”
Section: Re Sultsmentioning
confidence: 84%
“…Dental barotrauma is a term referred to the side effects of pressure changes on teeth, including failure of dental restorations, tooth fracture (barodontocrexis), or tooth pain (barodontalgia) [ 2 , 3 ]. It was reported that the dental side effects of scuba diving occur at diving depths of 10–25 m, a common depth for scuba diving [ 4 ]. Goethe et al [ 5 ], in a 10-year prospective study on the military divers who tolerated constant barometric changes, reported a 4-fold increase in the amount of extracted teeth and a ten-fold increase of teeth that need a prosthetic crown.…”
Section: Introductionmentioning
confidence: 99%
“…Such variations are significantly greater during diving as every descent of 10 m raises the pressure by another one atmosphere. [ 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 11 , 12 ] It affects the upper teeth than the lower teeth more commonly and many of the episodes appear on descent. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation